(untitled) (Shahroud Journal of Medical Sciences, 2019)
Background: Premenstrual syndrome (PMS) refers to a set of physical, psychological or behavioral symptoms occurring in ovulation cycles, which in some ways disturbs a person's activities. The aim of study was to investigate the relationship between previous use of contraceptive pills and psychological symptoms of PMS. Methods: This cross-sectional study was conducted among all female students of Shahroud University of Medical Sciences. Samples were selected by simple census and were provided a standard questionnaire for measuring the PMS. Significant level was set at 0.05. Results: 65.5% of the participants had some degree of PMS. The use of OCP significantly reduced some PMS related symptoms such as depression (Pvalue=0.039), sadness (Pvalue=0.012), sobering up (Pvalue=0.003) and anger (Pvalue=0.032). Conclusions: The results of this study showed the use of OCP can clearly and significantly reduce some of the symptoms associated with PMS, such as depression, sadness and sobering up, and anger. Key words: PMS, OCP, Psychiatry Symptoms.